2019
DOI: 10.4102/ac.v19i1.693
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the intentions of tourism providers and trade exhibition visitors to use technology: A technology acceptance model approach

Abstract: This article considered the use of technological tools by tourism trade exhibition visitors from a marketing perspective. Research purpose:The main aim of this article was to investigate the adoption and use of technology by tourism providers within the context of business events and exhibitions. Motivation for the study:To inform the tourism business practitioners about the efficient and appropriate uses of technological platforms in connecting and interacting with potential stakeholders at tourism events or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Ng, Shroff and Lim (2013) used TAM to explain why users accept or reject information technology, and they found that attitude towards usage evidenced a direct relationship with BI to use. Swart, Sotiriadis and Engelbrecht (2019) argued that influence along with attitude is an important factor to consider in determining tourists' BI. Moreover, Suki and Suki (2011) reinforced that attitudes have a strong, positive direct influence on intention to use mobile devices or services.…”
Section: Attitudes Towards the Use Of Instagram And Intention Towards The Use Of Instagrammentioning
confidence: 99%
“…Ng, Shroff and Lim (2013) used TAM to explain why users accept or reject information technology, and they found that attitude towards usage evidenced a direct relationship with BI to use. Swart, Sotiriadis and Engelbrecht (2019) argued that influence along with attitude is an important factor to consider in determining tourists' BI. Moreover, Suki and Suki (2011) reinforced that attitudes have a strong, positive direct influence on intention to use mobile devices or services.…”
Section: Attitudes Towards the Use Of Instagram And Intention Towards The Use Of Instagrammentioning
confidence: 99%